Finding new sewage sludge treatment solutions for the arctic city of Kiruna - Bauer, Torben; Lagerkvist, Anders (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2020)
As Sweden’s northernmost city, Kiruna has very particular demands for its sewage sludge treatment. This study tests hydrothermal carbonisation (HTC) as a treatment option for Kiruna to stabilize the sewage sludge, facilitate its transport by volume reduction and prepare the sludge for recovery of resources. The study consists out of an experimental part and a lifecycle assessment (LCA) development, which also gives options to use the results in other LCA scenarios incorporating HTC. Preliminary results show that HTC is a treatment that can fulfil Kiruna’s demands and that an optimization of the treatment’s settings can greatly increase the efficiency and effectiveness of the HTC treatment.